Economic viability of sugarcane cultivation: A comparative analysis - Abnave, Vikas Bajrang (Journal of Sugarcane Research, 2021)
Economic viability is one of the keystones of sugarcane sustainability. In today’s scenario, this means sugarcane growers who produce sugarcane sustainably must benefit from it. The economics of sugarcane cultivation is about finding logical, reasonable means of balancing individual economic self-interest with ecological and social integrity. Despite the increase in area and production of sugarcane, recently some concerns are emerging regarding farm profitability, sustainable use of farm resources and hike in input prices which have a direct and indirect influence on the cost of cultivation of sugarcane. Therefore, the objective is to analyse and compare the economic viability of sugarcane cultivation in major sugarcane producing states of India. The result indicates that the cultivation of sugarcane is profitable for Maharashtra but it involves more risk in terms of relatively less net income, as compared to other states. Moreover, the return per rupee spent was observed positive in both tropical and sub-tropical regions. The Sugar Trap makes the growers to stick with sugarcane cultivation due to some of the benefits received from the sugarcane crop such as relatively high profit, secure market (guarantee of purchase), less chance of crop failure, subsidized inputs, production system is based on contract farming model, etc. The study reports that, due to the longer duration of the crop, there is a hike in operation cost which warrants a technical solution.